Juridical Review Consumer Legal Against Labeling Of Food Products Based On Law No. 8 Year 1999 - Martina Lestari Ritonga (Journal of Law Science, 2021)
Consumer protection is in line with the development of the world economy. The rapid development of the world economy, especially in the trade sector, produces various types and variations of each type of goods and/or services that can be consumed. For consumers, information about goods and/or services is a basic need, before they use sources of funds to conduct consumer transactions with these goods and/or services. The right to correct information is one of the rights of consumers as regulated in Article 4 of Law no. 8 of 1999 concerning Consumer Protection. One source of the correct information is the label. In article 1 paragraph (3) of PP no. 69 of 1999 concerning Food Labels and Advertisements defines that what is meant by Food Labels is "any information regarding food in the form of pictures, writing, a combination of both or other forms that are attached to food, inserted into, affixed to or part of food packaging". From the definition of the label, it is known that the label contains information about the food produced. However, the problem of labeling, especially regarding food labels, has received less attention from consumers and business actors. Information that is not true and misleads consumers results in losses to consumers which ultimately results in legal consequences for business actors in taking responsibility for them. The type of research used in this research is normative legal research, which is a study that places norms as the object of research in this case is Law no. 8 of 1999. The type of approach used in this research is descriptive analytical approach, namely research based on one or two interrelated variables based on general theories/concepts that are applied to explain a set of data or show comparisons or relationships. Data collection is done by researching library materials (Library Research). Legal data analysis in this paper uses qualitative data. From the results of this research, it can be concluded that the provisions for labeling food products meet the principles of consumer protection and violations of food product labeling by business actors can be subject to civil, criminal and administrative responsibility.